On Rational Entrepreneurial Behaviour and the Demand for Investment - Treadway, A. B. (Review of Economic Studies, 1969)
Journal Article On Rational Entrepreneurial Behaviour and the Demand for Investment Get access A. B. Treadway A. B. Treadway Northwestern University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 2, April 1969, Pages 227–239, https://doi.org/10.2307/2296839 Published: 01 April 1969 Article history Received: 19 February 1968 Revision received: 05 August 1968 Published: 01 April 1969